2020
DOI: 10.1038/s41598-020-61381-9
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria as target to inhibit proliferation and induce apoptosis of cancer cells: the effects of doxycycline and gemcitabine

Abstract: Doxycycline has anti-tumour effects in a range of tumour systems. The aims of this study were to define the role mitochondria play in this process and examine the potential of doxycycline in combination with gemcitabine. We studied the adenocarcinoma cell line A549, its mitochondrial DNA-less derivative A549 ρ° and cultured fibroblasts. Treatment with doxycycline for 5 days resulted in a decrease of mitochondrial-encoded proteins, respiration and membrane potential, and an increase of reactive oxygen species i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 61 publications
2
63
0
Order By: Relevance
“…Inhibition of mitochondrial protein synthesis leads to reduced mitochondrial respiration and ATP production in mammalian cells, ultimately resulting in growth inhibition. Rapidly dividing cancer cells with high energy demands are more sensitive to antibiotics compared with non-cancerous cells, as confirmed in many in vitro and in vivo studies [ 31 , 38 ]. Similarly, in our study, HDFs, as non-cancerous skin cells, were less sensitive to antibiotics compared to melanoma cells.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Inhibition of mitochondrial protein synthesis leads to reduced mitochondrial respiration and ATP production in mammalian cells, ultimately resulting in growth inhibition. Rapidly dividing cancer cells with high energy demands are more sensitive to antibiotics compared with non-cancerous cells, as confirmed in many in vitro and in vivo studies [ 31 , 38 ]. Similarly, in our study, HDFs, as non-cancerous skin cells, were less sensitive to antibiotics compared to melanoma cells.…”
Section: Discussionmentioning
confidence: 91%
“…The endosymbiotic hypothesis proposes that mitochondria originated from bacteria [ 63 ]. Therefore, some antibiotics such as those used in the present study (TIG, DOX and AZI) reduce mitochondrial and bacterial translation by binding to their ribosomes [ 31 , 38 , 64 ]. Inhibition of mitochondrial protein synthesis leads to reduced mitochondrial respiration and ATP production in mammalian cells, ultimately resulting in growth inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note the same ndings were observed also in A375 cells (Additional le 4: Figure S4). Hereafter, we assess whether the depolarization of mitochondrial inner transmembrane potential as a marker of apoptosis (38,39) may occur in different combinatorial regimens. Data indicate that this was indeed the case.…”
Section: Resultsmentioning
confidence: 99%
“…Among the FDA-approved antibiotics that show the greatest potential in targeting mitochondrial cancer function are tigecycline and doxycycline. These molecules have been proven to reduce mitochondrial function and tumor stemness in many cancer models, both in vitro and in vivo [ 148 , 149 , 150 , 151 , 152 , 153 , 154 ]. In particular, in a clinical pilot study, doxycycline was shown to effectively reduce cancer stem cells in early breast cancer patients [ 155 ].…”
Section: Targeting Mitochondrial Metabolism In Cancermentioning
confidence: 99%